Single-cell analysis reveals the spatiotemporal effects of long-term electromagnetic field exposure on the liver - Zhang, Mingming; Lv, Zhichun; Zhao, Lingping; Zeng, Quan; Wu, Yunqiang; Zhou, Junnian; Xi, Jiafei; Pei, Xuetao; Wang, Haiyang; Li, Changyan; Yue, Wen (Frontiers in Cell and Developmental Biology, 2025)
IntroductionArtificial electromagnetic fields (EMFs) can impair the functions of several organs. The impact of long-term artificial EMF on the liver, the synthetic and metabolic center of the body, has become concerning. The aim of this study was to systematically evaluate the effect of long-term EMF exposure on the liver.MethodsMice were exposed to 2.45 GHz EMF daily for up to 5 months, and serum liver function test, lipidomic analysis, and histological analysis were performed to detect the general impact of EMF on the liver. Furthermore, EMF-induced liver transcriptome variations were investigated using single-cell RNA sequencing and a spatiotemporally resolved analysis.ResultsDifferent hepatic cells exhibited diverse sensitivities and response patterns. Notably, hepatocytes, endothelial cells, and monocytes showed higher sensitivity to electromagnetic radiation, with their lipid metabolic functions, immune regulation functions, and intrinsic functions disturbed, respectively. Moreover, transcriptomic alterations were predominantly observed in the hepatocytes and endothelial cells in peri-portal regions, suggesting a zonation-related sensitivity to EMF within the liver.ConclusionOur study provided a spatiotemporal visualization of EMF-induced alterations in hepatic cells, which ultimately elucidated the biological effects of EMF exposure.